(untitled) (Journal of history-rus, 2021)
The collection of documents collected during the life and work of outstanding historical figures of the country, figures of society, culture and art, scientists, heroes, who made a lot of efforts to update and revive the culture, language, Kazakh traditions and customs, is called the documents of the foundation of personal origin. The broad development of the Kazakh people, having joined the international community in the period of its current independence, has led intellectuals of Kazakh nationality to the world of sociopolitical relations at the international level. Archival documents about their services to the people, their contribution to the prosperity of the state are a precious treasure, an inexhaustible wealth for our national ideology. One of the most important tasks is to study and pass on their value to the next generations. The article analyzes the current state of the process of formation of funds of personal origin in the republican archives of Kazakhstan (Central State Archive, Presidential Archive, Central State Archive of Scientific and Technical Documentation) and the list of sources of acquisition of documents of personal origin. The analysis of the issues of categorization of the formed funds of personal origin is carried out. The criteria for the examination of the values of accepted documents of personal origin are set out. The system of grouping depending on the genre and type of documents of personal origin in the list is described. Proposals are made on completing the republican archives with documents of personal origin, determining their values, categorizing, improving the means of scientific reference apparatus. Key words: archive, personal documents, personal origin foundation, formation, inventory.